2021
DOI: 10.5194/essd-13-331-2021
|View full text |Cite
|
Sign up to set email alerts
|

A multi-scale daily SPEI dataset for drought characterization at observation stations over mainland China from 1961 to 2018

Abstract: Abstract. The monthly standardized precipitation evapotranspiration index (SPEI) can be used to monitor and assess drought characteristics with 1-month or longer drought duration. Based on data from 1961 to 2018 at 427 meteorological stations across mainland China, we developed a daily SPEI dataset to overcome the shortcoming of the coarse temporal scale of monthly SPEI. Our dataset not only can be used to identify the start and end dates of drought events, but also can be used to investigate the meteorologica… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
42
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 140 publications
(80 citation statements)
references
References 58 publications
0
42
0
Order By: Relevance
“…However, these limitations were addressed by the development of the standardized precipitation evapotranspiration index (SPEI) [22]. The following literature extensively summarizes recent SPEI based studies at a regional scale, temporal scale, types of datasets used and statistical method used [23][24][25][26][27][28][29][30][31][32][33][34][35][36]. Using different drought indices, most of these studies revealed that SPEI is most sensitive to drought conditions due to the evaporative demand component (as demonstrated in potential evapotranspiration (PET)) indicating SPEI importance as a favorable drought index.…”
Section: Introductionmentioning
confidence: 99%
“…However, these limitations were addressed by the development of the standardized precipitation evapotranspiration index (SPEI) [22]. The following literature extensively summarizes recent SPEI based studies at a regional scale, temporal scale, types of datasets used and statistical method used [23][24][25][26][27][28][29][30][31][32][33][34][35][36]. Using different drought indices, most of these studies revealed that SPEI is most sensitive to drought conditions due to the evaporative demand component (as demonstrated in potential evapotranspiration (PET)) indicating SPEI importance as a favorable drought index.…”
Section: Introductionmentioning
confidence: 99%
“…Both precipitation and air temperature can influence the drought conditions in cropland (Tigchelaar et al., 2018; Q. Wang et al., 2021). Standardised Precipitation‐Evapotranspiration Index (SPEI) can consider both precipitation and air temperature changes, and therefore we selected SPEI as the index for drought analysis.…”
Section: Methodsmentioning
confidence: 99%
“…Both precipitation and air temperature can influence the drought conditions in cropland (Tigchelaar et al, 2018;Q. Wang et al, 2021).…”
Section: Methodsmentioning
confidence: 99%
“…But the previous SPI can't monitor the drought below one month scale, and can't accurately identify the exact time of drought events. Therefore, based on the commonly used monthly SPI (Stagge et al, 2015) and the daily SPEI algorithm in our previous study (Wang et al, 2021b),…”
Section: Methodsmentioning
confidence: 99%
“…The determination method of similar events is whether SPI is within the same specified drought frequency (ATDF) of all sites (Wang et al, 2021b).…”
Section: Theory Of Runsmentioning
confidence: 99%